Linear Potentiometer Sensor-Based of Athlete Flexibility Measurement Tool - Firdausi, Dzihan Khilmi Ayu; Simbolon, Muhammad Eka Mardyansyah; Dwisaputra, Indra; Pebriandani, Catur (Jurnal Teknik Elektro Indonesia, 2024)
This study aims to develop a novel "sit and reach test" flexometer device utilizing a linear potentiometer sensor to quantitatively evaluate an individual's body flexibility. The innovation in this research lies in the utilization of electronic means to measure flexibility, replacing conventional manual methods. The device employs a linear potentiometer sensor that translates analog voltage into a digital value (ADC) and subsequently converts the digital data into distance measurements in centimeters (cm). The processed data, representing the distance measurements, is wirelessly transmitted to a personal computer (PC) for automatic capture and analysis. The design considerations prioritize modernity, practicality, effectiveness, and efficiency. The experimental outcomes demonstrate the efficacy of the developed tool. The readings from the linear potentiometer sensor exhibit a high linearity, indicated by an R2 value of 0.9999. The average error percentage is minimal, measuring at 0.17%. Moreover, the device allows for direct wireless transmission of data to a PC immediately after assessing an athlete's flexibility. This study not only introduces a novel electronic approach for assessing body flexibility but also validates its accuracy and efficiency through comprehensive testing and analysis.